Combined application of biochar and silicon fertilizer for improved soil properties and maize growth - Abu Bakar, Muhammad Wasil; Uddin, M. K.; Kasim, Susilawati; Zaibon, Syaharudin; Shamsuzzaman, S. M.; Haque, A. N. A.; Reza, A. (Technoscience Publications, 2024)
Biochar can be a good soil amendment to reduce the soil pH, increase crop growth rate, and improve the efficient use of fertilizer. Other than that, silicon fertilizer also would promote photosynthetic ability on plant development that would help to produce high yield. In this work, a series of experiments was conducted to observe the effect of rice husk biochar and silicon fertilizer on the maize growth rate and soil pH. A 45-day pot experiment in the greenhouse with three replicates of 9 experimental treatment combinations of RHB at two rates (5 and 2.5 t.ha-1) with silicon fertilizer at three rates (125%, 100%, 75%), sole biochar (10 t.ha t.ha-1), sole silicon fertilizer (100%) and control (NPK) to observe the best rate and combination to improve growth rate and change in soil chemical in acid soil. The result showed that the co-application of sole biochar and biochar with Silicon significantly improved growth development, increased photosynthesis rate, altered soil pH, and reduced Fe concentration compared to control. The plant height increased 88.35% from T4 (5 t.ha-1 RHB + 100% Si) compared to the control and the conductance was higher in T4 (0.53) followed by T8 (0.438) while T1 (0.071) recorded the lowest conductance. The shoot fresh weight was higher in T4 (127.83 g) followed by T8 (57.14 g). However, the weight increased by 343.7% at T4 followed by T8 (2.5 t.ha-1 RHB + 75% Si) at 98.33%. The highest pH increment of 1.24 units (T1 = 5.53, T4 = 6.77) of soil pH was noted from T4 (5 t.ha-1 RHB + 100% Si) compared to control (NPK), and the highest total Fe in soil was observed from T1 (442.30 mg.kg-1). The current study results showed that T4 (50% RHB + 100% Silicon) was the best treatment over the other rates of RHB and silicon increased plant height, photosynthetic rate, and biomass.